Predictors of High Motivation Score for Performing Research Initiation Fellowship, Master 1, Research Master 2, and PhD Curricula During Medical Studies: A Strobe-Compliant Article. Issue 5 (February 2016) - Feigerlova, Eva; Oussalah, Abderrahim; Fournier, Jean-Paul; Antonelli, Arnaud; Hadjadj, Samy; Marechaud, Richard; Guéant, Jean-Louis; Roblot, Pascal; Braun, Marc
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Translational research plays a crucial role in bridging the gap between fundamental and clinical research. The importance of integrating research training into medical education has been emphasized. Predictive factors that help to identify the most motivated medical students to perform academic research are unknown. In a cross-sectional study on a representative sample of 315 medical students, residents and attending physicians, using a comprehensive structured questionnaire we assessed motivations and obstacles to perform academic research curricula (ie, research initiation fellowship, Master 1, Research Master 2, and PhD). Independent predictive factors associated with high "motivation score" (top quartile on motivation score ranging from 0 to 10) to enroll in academic research curricula were derived using multivariate logistic regression analysis. Independent predictors of high motivation score for performing Master 1 curriculum were: "considering that the integration of translational research in medical curriculum is essential" (OR, 3.79; 95% CI, 1.49–9.59; P = 0.005) and "knowledge of at least 2 research units within the university" (OR, 3.60; 95% CI, 2.01–6.47; P < 0.0001). Independent predictors of high motivation score for performing Research Master 2 curriculum were: "attending physician" (OR, 4.60; 95% CI, 1.86–11.37; P = 0.001); "considering that the integration of translational research in medical curriculum is essential" (OR, 4.12; 95% CI, 1.51–11.23; P = 0.006); "knowledge of at least 2 research units within the university" (OR, 3.51; 95% CI, 1.91–6.46; P = 0.0001); and "male gender" (OR, 1.82; 95% CI, 1.02–3.25; P = 0.04). Independent predictors of high motivation score for performing PhD curriculum were: "considering that the integration of translational research in medical curriculum is essential" (OR, 5.94; 95% CI, 2.33–15.19; P = 0.0002) and "knowledge of at least 2 research units within the university" (OR, 2.63; 95% CI, 1.46–4.77; P = 0.001). This is the first study that has identified factors determining motivations and barriers to carry out academic research curricula among undergraduate and postgraduate medical students. Improving these 2 areas will certainly have an impact on a better involvement of the next generation of physicians in translational medicine.